Influence of the thermal treatment in the crystallization of NiWO4 and ZnWO4 - de Oliveira, A. L. M.; Ferreira, J. M.; Silva, Marcia R. S.; de Souza, Soraia C.; Vieira, F. T. G.; Longo, Elson [UNESP]; Souza, A. G.; Santos, Ieda M. G. (Springer, 2009)
NiWO4 and ZnWO4 were synthesized by the polymeric precursor method at low temperatures with zinc or nickel carbonate as secondary phase. The materials were characterized by thermal analysis (TG/DTA), infrared spectroscopy, UV-Vis spectroscopy and X-ray diffraction. NiWO4 was crystalline after calcination at 350 A degrees C/12 h while ZnWO4 only crystallized after calcination at 400 A degrees C for 2 h. Thermal decomposition of the powder precursor of NiWO4 heat treated for 12 h had one exothermic transition, while the precursor heat treated for 24 h had one more step between 600 and 800 A degrees C with a small mass gain. Powder precursor of ZnWO4 presented three exothermic transitions, with peak temperatures and mass losses higher than NiWO4 has indicating that nickel made carbon elimination easier.
Keywords: Wolframite; ZnWO4; NiWO4; Thermal treatment; Order-disorder